Prooxidant-oxidative homeostasis at different stages of the cyclic period of sexual activity in pigs - Ступарь, І. І. (Scientific Progress & Innovations, 2018)
The reproductive function of pigs largely depends on their breed. Most of this effect is developed in commercial pig production, when using modern systems of feeding and keeping, decreases individual physiological characteristics of sows in puberty. Inproperiate technology of keeping and breeding pigs causes a high level of infertility in the pigs. The aim of research is to determine the features of formation of prooxidant-antioxidant homeostasis at different phases of the cyclic period of sexual activity in pigs of different genotypes. The experiment was conducted on clinically healthy pigs of Large White breed (I group) and Pietrain (IІ group) selected on the basis of analogies. To evaluate the morphological and biochemical status of pig blood it was taken the anterior hollow vien at different phases of the sexual cycle – estrus and diestrus. During the research period, acceleration of peroxidation was detected that is indicative of activity of superoxide dismutase and catalase in Large White breed by 45.1% and 11.5%, it is by 22.1% and 20% in Pietrain breed, increasing concentration diene conjugates and TBA-active complexes in first genotype, respectively by 29.6% and 25.9%, and in second one is by 30.6% and 30%. We have diagnosed a significant impact of the genotype on an activity of superoxide dismutase in serum of pigs, preponderated in the Large White breed relatively to Pietrain at the phase of diestrus: 23.9% and 75.58% and at estrus phase: 75.58% (p<0.001). The number of secondary products of lipid peroxidation (TBA-active complexes) in pigs of Pietrain breed is higher than in Large White breed. The content of beta-prebeta lipoprotein has increased with the onset of sexual arousal in the first group of animals by 29.4%, the second one is by 19.4%, but it is higher in pigs of Large White breed. In comparison with estrus phase, a significant decrease in the number of reduced glutathione is found at diestrus phase: in the animals of Large White breed – 29.7%; in Pietrain breed – increased by 48%. It has been dicoverd that during estrus the concentrations of ascorbic and dehydroascorbic acids in Large white breed increases in 1.9 and 2.2 times, and in Pietrain breed – only 1.2 and 1.4 times in comparison with the period of anestrus. Moreover, during the period the content of oxidized forms of ascorbic acid remaines higher than restored one in both genotypes. It is noticed the decrease in erythrocyte membrane stability to peroxide hemolysis during this period: in the animals Large White breed – 21.3%, in Pietrain breed – 33.3%. At all studied phases of the sexual cycle the contrast changes in the amount of steroid and thyroid hormones is found. The concentration of estradiol at estrus phase in Large White breed increased by 21.6% and 23.2% – in Pietrain breed, with typical progesterone levels decrease, respectively, in the first breed is in 4 times (p<0.01) and in the second one is in3.2 times (p<0.05). Hormone balance in Pietrain breed during estrus significantly affectes the state of prooxidant-antioxidant homeostasis, namely, the amount of progesterone significantly correlates directly with the diene conjugates (r = 0.84), TBA-active complex (r = 0.68), the activity of antioxidant enzymes – superoxide dismutase and catalase, respectively r = 0.82 and r = 0.73. Significant correlations between progesterone and diene conjugates (r = 0.53), TBA-active complex (r = 0.95) have been found in animals of Large White breed. The content of estradiol is in proportion with the diene conjugates (r = 0.84), TBA-active complex (r = 0.75), superoxide dismutase (r = 0.35).